Impact of neutrophil-secreted myeloid related proteins 8 and 14 (MRP 8/14) on leishmaniasis progression. - Irazú Contreras; Marina T Shio; Annabelle Cesaro; Philippe A Tessier; Martin Olivier (Public Library of Science (PLoS), 2013)
The myeloid-related proteins (MRPs) 8/14 are small proteins mainly produced by neutrophils, which have been reported to induce NO production in macrophages. On the other hand, Leishmania survives and multiplies within phagocytes by inactivating several of their microbicidal functions. Whereas MRPs are rapidly released during the innate immune response, their role in the regulation of Leishmaniasis is still unknown. In vitro experiments revealed that Leishmania infection alters MRP-induced signaling, leading to inhibition of macrophage functions (NO, TNF-α). In contrast, MRP-primed cells showed normal signaling activation and NO production in response to Leishmania infection. Using a murine air-pouch model, we observed that infection with L. major induced leukocyte recruitment and MRP secretion comparable to LPS-treated mice. Depletion of MRPs significantly reduced these inflammatory events and augmented both parasite load and footpad swelling during the first 8 weeks post-infection, as also observed in MRP KO mice. On the contrary, mouse treatment with recombinant MRPs (rMRPs) had the opposite effect. Collectively, our results suggest that rapid secretion of MRPs by neutrophils at the site of infection may protect uninfected macrophages and favor a more efficient innate inflammatory response against Leishmania infection. In summary, our study reveals the critical role played by MRPs in the regulation of Leishmania infection and how this pathogen can subvert its action.